Numerical analysis of the freeze-thaw performance of cementitious composites that contain phase change material (PCM). (5th May 2018) - Esmaeeli, Hadi S.; Farnam, Yaghoob; Haddock, John E.; Zavattieri, Pablo D.; Weiss, W. Jason
Abstract: We employ a numerical methodology to predict the freeze-thaw performance of cementitious composites containing lightweight aggregates (LWAs) impregnated with phase change material (PCM) as thermal energy storage (TES) agent. The governing equation for heat transfer is combined with homogenization techniques to predict the temperature and associated heat flow for cementitious materials during the phase transition of the PCM. The material properties of the cementitious composite and heat dissipation behavior during thermal cycling were characterized using a small-scale longitudinal guarded comparative calorimeter (LGCC) test. Phase transitions associated with freezing/melting of PCM occurs gradually over a narrow temperature range. Pore size effect of LWA on freezing and melting behavior of PCM was found to be relatively small. This approach is extended to the prediction of the thermal energy storage capacity of PCM on improving the freeze-thaw performance of concrete specimens exposed to realistic thermal conditions at various locations in the United States. Graphical abstract: Unlabelled Image Highlights: Finite difference method along with homogenization technique was used for cementitious composites with phase change material. The model was validated by data obtained from two experimental tests for mortar and concrete materials. Phase change material showed gradual transition over a narrow temperature range, while aggregate pores had negligible effect. Use of phase change material decreased the time and depth of freezing within the concrete pavements in the United States. This technology was most effective across the east and Pacific Northwest.